THE MEDIATING ROLE OF BRAND SWITCHING INTENTION IN THE RELATIONSHIP BETWEEN SERVICE QUALITY AND PURCHASE DECISION: EVIDENCE FROM INDIHOME CUSTOMERS IN PEKANBARU - Bord Nandre Aprila; Sarli Rahman; Siti Salwa Kurnia; Dedy Novrizal; Fery Martias (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
Penelitian ini bertujuan menganalisis pengaruh kualitas pelayanan terhadap keputusan pembelian serta menguji peran mediasi brand switching intention pada pelanggan IndiHome di Kota Pekanbaru. Penelitian menggunakan pendekatan kuantitatif dengan sampel sebanyak 151 pelanggan yang dipilih melalui teknik accidental sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan metode Partial Least Squares-Structural Equation Modeling (PLS-SEM) menggunakan SmartPLS. Hasil penelitian menunjukkan bahwa kualitas pelayanan berpengaruh negatif dan signifikan terhadap brand switching intention serta berpengaruh positif dan signifikan terhadap keputusan pembelian. Sementara itu, brand switching intention berpengaruh negatif namun tidak signifikan terhadap keputusan pembelian. Hasil uji mediasi menunjukkan bahwa brand switching intention tidak memediasi pengaruh kualitas pelayanan terhadap keputusan pembelian. Temuan ini menegaskan bahwa kualitas pelayanan merupakan faktor penting dalam meningkatkan keputusan pembelian dan menurunkan kecenderungan pelanggan untuk beralih ke penyedia layanan lain. Oleh karena itu, peningkatan kualitas pelayanan perlu menjadi prioritas perusahaan untuk mempertahankan daya saing di industri layanan internet broadband. This study aims to examine the effect of service quality on purchase decisions and investigate the mediating role of brand switching intention among IndiHome customers in Pekanbaru, Indonesia. A quantitative research approach was employed, involving 151 respondents selected through an accidental sampling technique. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that service quality has a negative and significant effect on brand switching intention, indicating that higher service quality reduces customers' tendency to switch to competing service providers. In addition, service quality has a positive and significant effect on purchase decisions, suggesting that improved service quality enhances customers’ willingness to choose and continue using IndiHome services. Meanwhile, brand switching intention has a negative but insignificant effect on purchase decisions. Furthermore, the mediation analysis demonstrates that brand switching intention does not significantly mediate the relationship between service quality and purchase decisions. These findings highlight the critical role of service quality in enhancing purchase decisions and reducing customers’ propensity to switch to alternative service providers. Therefore, improving service quality should be prioritized as a strategic initiative to strengthen competitiveness and sustain customer retention in the increasingly competitive broadband internet service industry.